2007
DOI: 10.1007/s10608-006-9098-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Integrity in Multiple Family Groups: Psychometric Properties and Relationship with Schizophrenia Client and Caregiver Outcomes

Abstract: Multiple family group treatment (MFGT) is an evidence-based cognitive behavioral psycho-education and problem-solving intervention for the management of schizophrenia. Despite empirical support for the efficacy of MFGT, there is no psychometric tool for measuring treatment integrity in MFGT. In addition, research has not examined the impact of treatment integrity on client and family outcomes. The psychometric properties of a clinician integrity measure and its relationship to client and family outcomes was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Since the 2002 review paper, regarding FPE with adults with schizophrenia (MacFarlane, Dixon, Lukens, & Lucksted, 2002), there were a variety of new RCTs. There was a significant study in Washington State involving 97 consumers and their family members that replicated previous work showing that, compared with standard care, MFG-FPE reduced relapse, symptomatology, and hospitalization with no net increase in outpatient services over 3 years (McDonell et al, 2007).…”
Section: Family Psycho-education For Major Mental Illnessmentioning
confidence: 56%
“…Since the 2002 review paper, regarding FPE with adults with schizophrenia (MacFarlane, Dixon, Lukens, & Lucksted, 2002), there were a variety of new RCTs. There was a significant study in Washington State involving 97 consumers and their family members that replicated previous work showing that, compared with standard care, MFG-FPE reduced relapse, symptomatology, and hospitalization with no net increase in outpatient services over 3 years (McDonell et al, 2007).…”
Section: Family Psycho-education For Major Mental Illnessmentioning
confidence: 56%
“…Finally, for many mental health interventions, poor fidelity to a core model has been found to compromise outcomes (for example, the study by Bond & Salyers, 2004). One study found a strong relationship between fidelity and positive and negative symptom outcomes for FPE after 2 years (McDonell et al., 2007). Most FPE studies, however, do not report any information on the fidelity of their intervention’s delivery to whichever model of FPE they are using.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, McDonell et al. () documented a nonlinear decline in outcome as fidelity to the MFG‐FPE model declined; only high fidelity MFG implementation replicated relapse results, unlike even moderate, let alone low, fidelity. Clearly, as in other advanced methods in medicine and technology, advances in outcomes require adherence to the methods used originally to achieve them.…”
Section: Mediating Effectsmentioning
confidence: 99%